Fermented Vinegars from Apple Peels, Raspberries, Rosehips, Lavender, Mint, and Rose Petals: The Composition, Antioxidant Power, and Genoprotective Abilities in Comparison to Acetic Macerates, Decoctions, and Tinctures - Małgorzata Kalemba-Drożdż; Inga Kwiecień; Agnieszka Szewczyk; Agnieszka Cierniak; Agata Grzywacz-Kisielewska (MDPI AG, 2020)
Acetic fermentation is a method for processing plant material which has been known since antiquity. Balsamic and apple cider vinegars are investigated as antibacterial, anti-obesity, and anti-diabetic remedies. However, there is little information about vinegars fermented from aromatic herbs and edible plants. The aim of this study was to compare extracts used for culinary and medicinal purposes according to their composition, antioxidant power, and genoprotective properties. Fermented vinegars, acetic macerates, decoctions, and tinctures in 70% ethanol from raspberries, apple peels, rosehips, lavender, mint, and rose petals were prepared. Polyphenols, ascorbate, carotenoid concentrations, and antioxidant power were analyzed. The polyphenols were identified using HPLC (high-performance liquid chromatography). The genoprotective properties were measured using a comet assay on lymphocytes. Fermented vinegars were poorest in phytochemicals in comparison to tinctures, decoctions, or acetic macerates, although they contained the highest concentration of metal ions. The antioxidant abilities were correlated to the phenolic content of extract. None of the extracts induced DNA damages into lymphocytes. The rosehip and rose petal extracts revealed the highest genoprotective abilities, while mint and apple fermented vinegars and decoctions had the lowest. Fermented vinegars are not a rich source of phytochemicals and they show weak genoprotective abilities, but, in increasing demand for antioxidants, any form of phytochemical sources is an added-value in diet.